Los créditos sin garantía y su incidencia económica financiera en las empresas comercializadoras de fertilizantes en el valle Jequetepeque, período 2011. - Egoavil Garcia, Genoveva Raquel (2012)
This paper titled "loans without guarantees and its economic impact marketers FINANCIAL IN THE VALLEY FERTILIZER Jequetepeque period 2011" was developed in the Valley Jequetepeque trying to solve the following problem main impact How unsecured claims in the economic and financial situation in fertilizer trading companies in the valley Jequetepeque period 2011? The overall objective of this research was to "prove as unsecured loans impact on economic and financial situation in the trading companies in the Valley Fertilizer Jequetepeque, period 2011." The hypothesis has been raised is the following that "unsecured loans adversely affect the economic and financial situation in the trading companies in the Valley Fertilizer Jequetepeque". This thesis was supported by documentary information the company gave Agricultural Franccesca SA, and also statistical analysis, data and analysis to financial statements, so that right through them to visualize the impact caused unsecured lending .